If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(x)=2x+9(3)
We move all terms to the left:
9(x)-(2x+9(3))=0
We get rid of parentheses
9x-2x-93=0
We add all the numbers together, and all the variables
7x-93=0
We move all terms containing x to the left, all other terms to the right
7x=93
x=93/7
x=13+2/7
| 2(h+7)=14+2h | | y32=81 | | 0-3x10÷(-3)=10 | | x-3x+2=-23 | | (n+9)(n-1)=0 | | -5/25*c=1 | | 3b-2.3=5 | | -5x+9+6x=5+x+4 | | 6x=x+84 | | 4.5(8-x)+36=102–2.5(3x+24) | | -44-5(-2x+2)=-70 | | 3x=27+-15x | | 0.50(2+v)=0.30(2)+0.75v | | 64/16=g/18.5 | | -6=-x+3x-2 | | 9/2(8-x)+36=102–5/2(3x+24) | | 2x+x=4860 | | -6x+10+4x=26 | | 6x-3x-12=-18 | | -3=-3y-43 | | -3=-3y-4 | | 4(x-5)-3x=3(x-2) | | 3x-1x-4=-6 | | 3/25=y/20 | | 2x+x=4880 | | 4x-35=x×1 | | -7x+2+x=68 | | 409-x=2.06 | | 4x=2(3x-9) | | -17+x/5=-8 | | 75=72.6+0.17(b-1975) | | 4x-3x+12=2x+2 |